2018
DOI: 10.1038/nrgastro.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR–Cas-related technologies in basic and translational liver research

Abstract: CRISPR–Cas9 has revolutionized biomedical research. Studies in the past few years have achieved notable successes in hepatology, such as correction of genetic disease genes and generation of liver cancer animal models. Where does this technology stand at the frontier of basic and translational liver research?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Cas13 differs from Cas9 because binds and cleaves RNA instead of DNA, which could be a promising tool for RNA-directed therapies [186]. Several preclinical studies used CRISPR effectors to edit DNA or RNA but efficient translation into clinical practice remains to be verified [187,188]. Small molecules .…”
Section: Lncrnas Diagnostic Prognostic and Therapeutic Perspectivesmentioning
confidence: 99%
“…Cas13 differs from Cas9 because binds and cleaves RNA instead of DNA, which could be a promising tool for RNA-directed therapies [186]. Several preclinical studies used CRISPR effectors to edit DNA or RNA but efficient translation into clinical practice remains to be verified [187,188]. Small molecules .…”
Section: Lncrnas Diagnostic Prognostic and Therapeutic Perspectivesmentioning
confidence: 99%
“…We and others recently reported that CRISPR can correct this Fah mutation through HDR [16][17][18] or allelic exchange 19 . Following correction by CRISPR, liver cells expressing the Fah enzyme, through their selective advantage, expand and repopulate the liver 14 .…”
mentioning
confidence: 95%
“…The working mechanism of the CRISPR/Cas system differs from other genome editing platforms, for it uses an RNA molecule more than a protein to recognize DNA [25]. CRISPR/Cas systems are classified into three types (I-III).…”
Section: Overview Of Crispr/cas9 Techniquementioning
confidence: 99%
“…Additionally, the genome editing efficiency is also affected by non-homologous end joining (NHEJ) and homology-directed repair (HDR) DNA repair mechanisms [4]. Studies have demonstrated that the HDR rate is lower than the NHEJ rate in the liver, limiting the therapy of diseases requiring gene editing by HDR [25]. Thankfully, the latest research has revealed the Fanconi anemia pathway to make CRISPR/Cas9 work better in almost all cells [73].…”
Section: Current Advantages and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation